Comparative evaluation of frictional resistance of extracoronal attachments of different designs and lengths in fixed partial denture: A finite element analysis - Minal Sanjay Kumthekar; Pronob Kumar Sanyal; Shivsagar Tewary (Wolters Kluwer Medknow Publications, 2021)
Aim: The purpose of the study was to evaluate the frictional resistance and the vertical force required to achieve the frictional resistance for different length and designs of extracoronal attachments used in fixed partial denture (FPD). Setting and Design: Finite element analysis. Materials and Methods: Four different designs and five different lengths (3 mm, 3.5 mm, 4 mm, 4.5 mm, and 5 mm) of extracoronal attachments for FPD were selected from different manufacturers. Three-dimensional models of all the samples were simulated using Catia V5 software. The properties were incorporated to the software to simulate the clinical conditions. The frictional resistance and the vertical force required to achieve frictional resistance were analyzed using ANSYS workbench 15.0 finite element software. Statistical Analysis Used: ANOVA and Tukey's post hoc test. Results: The mean microhardness of the Variolink N resin cements were significantly higher than Panavia SA ones (P < 0.001). Variolink N cements exhibited lower sorption/solubility than Panavia SA resin cements (P < 0.05). The ceramic shade had a significant influence on the microhardness of both cements (P < 0.001) but had no significant effect on the sorption/solubility of resin cements (P > 0.05). Conclusion: Interposition of monolithic zirconia decreases the microhardness of resin cement especially Panavia SA. The microhardness decreased in Variolink N with the increase in the chroma saturation of ceramics. However, in Panavia SA, it was altered by the shades. For both cements, there were no statistical differences between the sorption/solubility. There was a reverse correlation between microhardness and water sorption/solubility of both cements.